‘Not in touch’: Nonverbal communication and frontline perceptions of inter-organizational justice in parole work - Taylor, Micheal P (Theoretical criminology, 2024)
We conducted semi-structured interviews with 17 parole officers working in Canadian federal correctional services to understand how their perceptions mediate well-being. Our study elucidates dimensions of interactional justice related to three elements of nonverbal communication theory (i.e. haptics, proxemics and kinesics). By centralizing the voices of our participants, we show how nonverbal communication theory mediates organizational citizenship behaviour and the multi-construct concepts of justice. Framing interpretations with how public employees interact, we reflect on the impacts to which correctional workers—as public safety employees—perceive their criminal justice employment. We argue exploration into nonverbal communication, and a deeper understanding of how correctional services govern, may provide structural accountability by closing a loop in organizational knowledge flow.